Reizwort „Darwin“: Eine komparatistische Diskursanalyse zu Wissenschaftskonzepten in zwei gegenwärtigen didaktischen Kontroversen, nebst einem historischen Exkurs - Meier, Markus (International Dialogues on Education Journal, 2015)
Since schools have left the patronage of religious institutions, the sciences have become their point of reference as far as their didactic content is concerned, the state as far as their form (administration, financiation etc.) is concerned. The present paper aims to show, how political and/or religious interests try to interfere with the scientific orientation in secondary and tertiary education, referring to the case of Charles Darwins theory of evolution. In an introductory analogy, the implementation of “Rassenkunde (race education)” during the Third Reich is reconstructed and contrasted to attempts to install “creationism” resp. “gender-studies” in education today. Both intentions are concludingly evaluated in respect to their scientific and political foundations and implications.